TERRORISM HABITUS REPRODUCTION IN INDONESIA (STUDY OF PIERRE BORDIEU'S THOUGHT IN POTRAYING TERROR BEHAVIOR IN INDONESIA) - sopian - tamrin; Idham Irwansyah; Mario Mario; Arisnawawi Arisnawawi (LPPM Universitas PGRI Sumatera Barat, 2021)
The problem of terrorism in Indonesia is clearly troubling all circles to any social aspect. Efforts made by the government are still predominantly spontaneous and repressive. Besides, the explanation of social theory in explaining terror behavior in Indonesia is still not able to provide a broad and in-depth insight, so this problem has solved on the phenomena that appear on the surface only. Therefore, it is important to find a complex theoretical explanation that can be overcome to the root. The focus of the study is to analyze how the social reproduction of terror behavior in Indonesia with the perspective of Pierre Bourdieu. The descriptive method with a qualitative approach was used in this research. The method of data collection is done by using observation, interview and documentation techniques. The results of this study show that terror behavior in Indonesia is an inner thought that lasts for quite a long time. The practice of terror does not happen instantly due to a certain momentum reaction. The reproduction of the terror behavior practice indicates the existence of a well-maintained habitus in the community. Their struggle is also inseparable from the existence of social capital and economic capital for the actors. Religious tendencies are used as a media that is considered appropriate to perpetuate the socialization process.